Visual perception of abstract art images in extraversion and ambiversion at P300 and N200 - Antoine, Audrey Antoine A/P Max (2022)
INTRODUCTION: Over decades, psychologist has been trying to bridge the gap between art preference and personality. Art and personality as we know are difficult areas to quantify. Therefore, social neuroscientist tried bridging the gap between art, personality, arousal intensity and neural substrates. OBJECTIVES: This study aims to investigate the differences of neural substrates in abstract art of extraverts and ambiverts in the processing of emotion using the Event Related Potential (ERP) as well as its source of localization of N200 and P300 in the emotional processing of the two personalities – extraverts and ambiverts. METHODOLOGY: A total of 28 participants (N=14 for each personality) aged 18- 25 years old were recruited from USM Health Campus, Kubang Kerian and Kota Bharu area for this cross-sectional study. As for the pictures used,12 pictures (6 abstract, 6 non-abstract) were taken randomly from the International Affective Picture System (IAPS) based on the normative value of IAPS (low and moderate). An eventrelated potential (ERP) recording was done using the 128 HydroCel Geodesic Sensor Net on participants during active viewing of abstract and non-abstract visual stimuli. RESULTS: A 2x3 mixed ANOVA results showed that there was a significant difference in the main effect (the effect of types of pictures, regardless of personality type) and between subject effect (type of personality, regardless type of pictures) on the P300 latency of the Fz electrode, a significant difference main effect for both Pz and Oz electrode for the P300 amplitude and a significant difference in the main effect in the Oz electrode of the N200 amplitude where p < 0.01. The source of localization for both N200 and P300 lies in two main lobes. The most common lobe was the occipital lobe as this study is based on visual perception, followed by the temporal lobe. In this study, two different Broadmann areas (B.A) was identified for the source of localization for N200 and P300 in extraversion and ambiversion which is B.A 18 and 38. The specific areas identified are fusiform gyrus, inferior occipital gyrus, lingual gyrus and superior temporal gyrus. CONCLUSION: In conclusion, ambiverts have a higher emotional response than extraverts at the Pz electrode in the P300 latency for non-abstract art images. This may be due to non-extraverts preferences on semantic content images or better known as complex structured images that can be found in non-abstract art images. As all the participants that volunteered in this study were not from an art expertise background, the preference of non- abstract art is understandable.